Incidence of Dermatophytosis Based on Age and Gender at The Regional General Hospital in Gianyar District Hospitals - Widhidewi, Ni Wayan; Purnama, Ni Kadek Ari; Budiapsari, Putu Indah; Widiawati, Sayu (Muhammadiyah Medical Journal, 2023)
Background: Dermatophytosis is a superficial fungal infection caused by filamentous fungi that attack the keratinized tissue of the skin, nails, and hair. The clinical manifestations of dermatophytosis, in addition to depending on the source host factors, such as age, sex, and race, are significant epidemiological factors. However, the relationship of infection susceptibility remains unclear. Purposes: This study aimed to determine the relationship between age and sex and dermatophytosis incidence in Gianyar Regency. Methods: This study was observational with a cross-sectional design using 200 samples divided into 100 dermatophytosis patients and 100 non-dermatophytosis patients. Statistical analysis of the data used was a chi-square test with 95%CI. Results: The majority of patients with dermatophyte infections were 19 years old (74%), female (57%), and tinea corporis (36%). The chi-square test showed that there was a significant relationship between age and sex with the incidence of dermatophytosis (p = 0.025; OR = 1.978; 95% CI = 1.087-3.599 and p = 0.003; OR = 2.357; 95% CI = 1.334-4.162). Conclusion: It can be concluded that older age and female tend to suffer dermatophytosis.